Adsorptive removal of Zn (II) from synthetic wastewater using rubber seed shell charcoal - Mohan Thomas; Anitha Pious; George Sebastian; Philip K C (Pollution Research, 2011)
Charcoal samples were prepared from rubber seed shell, an agricultural waste, for the removal of Zn (II) ions. The adsorption characteristics of Zn (II) ions from aqueous solution on to activated rubber seed shell charcoal (RSSC), acid treated rubber seed shell charcoal (ARSSC), chitosan coated rubber seed shell charcoal (CCRSSC), and chitosan coated acid treated rubber seed shell charcoal (CCARSSC) were investigated. The effect of pH of zinc solution, adsorbent dose and contact time on adsorption rates were studied in batch experiment. Results showed that chemically modified adsorbants with oxidizing agents or chitosan have better zinc (II) removal capabilities than the untreated on es. The removal efficiency was found to be in the order (CCARSSC)> (CCRSSC)> (ARSSC)>(RSSC). The optimum pH was found to be 7. The equilibrium data for the adsorption of zinc (II) were analysed in the light of Langmuir and Freundlich isotherm models.
Source Year: 2011
Keywords: Adsorption; Biosorbent; Chitosan; Isotherm; Rubber seed shell charcoal